Bacteriophages Alternatives to Antibiotics and Beyond - Suárez, Pilar García; Fernández, Lucía (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There is talk of an upcoming antibiotic armageddon, with untreatable post-operative infections, and similarly untreatable complications after chemotherapy. Indeed, the now famous "O'Neill Report" (https://amr-review.org/) suggests that, by 2050, more people might die from antibiotic-resistant bacterial infections than from cancer. While we are still learning all the subtle drivers of antibiotic resistance, it seems increasingly clear that we need to take a "one health" approach, curtailing the use of antibiotics in both human and veterinary medicine. However, there are no new classes of antibiotics on our horizon. Maybe something that has been around "forever" can come to our rescue-bacteriophages! Nevertheless, it is also necessary to do things differently, and use these new antimicrobials appropriately. Therefore, an in-depth study of bacteriophage biology and case-by-case applications might be required. Whilst by no means comprehensive, this book does cover some of the many topics related to bacteriophages as antimicrobials, including their use in human therapy and aquaculture. It also explores the potential use of phage endolysins as substitutes of antibiotics in two sectors where there is an urgent need-human therapy and the agro-food industry. Last but not least, there is an excellent perspective article on phage therapy implementation.